THE IMPACT OF PRODUCT QUALITY AND PRODUCT INNOVATION ON THE MARKETING PERFORMANCE OF COSMETIC RETAIL STORES IN KEDIRI: MEDIATION OF MARKET ORIENTATION - Misbachul Nur Wahid; Lina Saptaria (SOSIOEDUKASI, 2025)
This study investigates the influence of product quality and product innovation on marketing performance, with market orientation serving as a mediating variable in cosmetic retail stores in Kediri. Employing a quantitative explanatory research design, data were gathered through questionnaires distributed to cosmetic store owners, managers, and supervisors with a minimum of one year of operational experience. The sample was determined using purposive sampling, and the data were analyzed using Structural Equation Modeling (SEM-PLS) with SmartPLS 4. The results indicate that both product quality and product innovation exert a positive and significant effect on market orientation and marketing performance. Market orientation is also found to positively and significantly enhance marketing performance while mediating the relationship between product quality, product innovation, and marketing performance. These findings imply that superior product quality and continuous innovation, when aligned with strong market orientation, can substantially improve the marketing performance of cosmetic retailers. The study’s contribution is reinforced by its novelty, namely the empirical testing of a market‐orientation mediation model within the specific context of regional cosmetic retailing—an area that has received limited scholarly attention. The research extends marketing theory by offering empirical evidence from a unique industry and regional setting, while also providing practical insights that can guide strategic decision-making for cosmetic retail businesses.